Associations of screen time with symptoms of stress, anxiety, and depression in adolescents - Maria Carolina Juvêncio Francisquini; Thais Maria de Souza Silva; Géssika Castilho dos Santos; Rodrigo de Oliveira Barbosa; Pedro Henrique Garcia Dias; Ariel Bello Ruiz; Jadson Marcio da Silva; Antonio Stabelini Neto (Sociedade de Pediatria de São Paulo, 2024)
ABSTRACT Objective: To examine the associations between self-reported screen time and symptoms of stress, anxiety, and depression in adolescents. Methods: A cross-sectional study was conducted with 982 adolescents aged between 12 and 15 years, enrolled in public schools in Jacarezinho (PR), Brazil. Screen time was assessed by the question "Considering a typical day, how much time do you spend watching TV, playing videogame, using computer or smartphone?" The DASS-21 questionnaire (short form) was used to assess symptoms of depression, anxiety, and stress. Crude and adjusted analyses (age, sex, and maternal level of education) between screen time and mental disorders symptoms were performed using general linear regression models, with Poisson distribution, with significance level at p<0.05. Results: Higher depressive symptoms were observed in adolescents who reported screen time of 4-6 hours/day (PR 1.35, 95%CI 1.13-1.61) and ≥6 hours/day (PR 1.88, 95%CI 1.62-2.19), compared with their pairs with <2 hours/day. The same was observed for anxiety symptoms with screen time of 4-6 hours/day (PR 1.23, 95%CI 1.04-1.46) and ≥6 hours/day (PR 1.50, 95%CI 1.28-1.77); and stress, with 4-6 hours/day (PR 1.25, 95%CI 1.08-1.44) and ≥6 hours/day (PR 1.49, 95%CI 1.30-1.71), also compared with their pairs with <2 hours/day. Conclusions: Screen time was positively associated with depressive, anxiety, and stress symptoms in adolescents. Special attention should be given to those who spend more than four hours a day in front of a screen.